Assessment of the Construction Welding Process. (2017) - Mazur, Magdalena
Abstract: The paper presents the stages of quality control of welding processes, which is implemented through: visual inspection, testing, measurement using a checking apparatus, patterns and comparison of the results with clasped values (acceptance criteria). These activities are carried out to determine the compatibility of the produced welded joint with the objectives of quality resulting from the technology qualification process. The aim of the study is to analyze the level of quality manufacturing processes carried out in the company relating to the production of welded structures including analysis of the used materials quality.